Fluorination Induced Donor to Acceptor Transformation in A1–D–A2–D–A1-Type Photovoltaic Small Molecules - Zhou, Ruimin; Xia, Benzheng; Li, Huan; Wang, Zhen; Yang, Yang; Zhang, Jianqi; Laursen, Bo W.; Lu, Kun; Wei, Zhixiang (Frontiers in Chemistry, 2018)
With the development of diversity of non-fullerene acceptors, it is found that there is no clear boundary between electron donors and electron acceptors. Modulation of the electron donating and withdrawing properties of organic semiconductors is necessary for organic photovoltaics research. In this work, we designed and synthesized three A1–D–A2–D–A1-type (A represents acceptor unit and D represents donor unit) small molecules, named as M-0F, M-1F, and M-2F, respectively containing zero, one, and two fluorine atoms in the terminal acceptor segments (A1), respectively. Fluorination substitution was found to be able to downshift the HOMO and LUMO energy level, red-shift the absorption, and enhance the electron mobility. The M-0F exhibited the highest efficiency of 5.99% as a donor in fullerene-containing system and the lowest efficiency of 0.58% as an acceptor in fullerene-free system. While the M-2F performed the lowest efficiency of 0.97% as the donor and the highest efficiency of 2.65% as the acceptor. The electron-donating and electron-withdrawing property of M-1F are in-between that of M-0F and M-2F. Among the three molecules, the electron mobility is increased while the hole mobility is decreased with increasing fluorination. This work provides a typical example of tuning of the electron donating and withdrawing property without changes to the backbone of the conjugated molecules, which is important for further designing high performance solution processable small molecules.